Emerging drugs for the treatment of sepsis. (2nd January 2016) - Heming, Nicholas; Lamothe, Laure; Ambrosi, Xavier; Annane, Djillali
ABSTRACT: Introduction : The incidence of sepsis, the systemic inflammatory response of the host to an infectious insult, has steadily increased over past decades. This trend is expected to continue. Sepsis is a leading cause of death and disability worldwide. Treatment relies on antibiotics associated to source control and supportive care. Major progress has been made in the understanding and overall management of sepsis. However, there is no specific treatment for sepsis. Areas covered : We searched PubMed and the ClinicalTrials.gov site for English language reports of phase II and III clinical trials pertaining to the field of sepsis. The current review provides a summary of promising candidate treatments for sepsis. We broadly separated candidate drugs into three distinct categories: Blood purification techniques, immunomodulatory drugs and treatments targeting other systems including the heart, the endothelium or coagulation. Expert opinion : Efforts to identify an efficient treatment for sepsis are hampered by the broad definition of the syndrome associated with major heterogeneity between patients affected by sepsis. The characterization of homogeneous groups of patients, through biological or clinical markers is unfortunately lacking. Current research remains active. Candidate drugs for sepsis include hemoperfusion with polymyxin B coated fibre devices, modulation of the immune system with treatments such as hydrocortisone, intravenous immunoglobulins, mesenchymal stem cells, GM-CSF or interferon gamma. Candidate drugs acting on the cardiovascular system include short acting beta 1 blockers, levosimendan or selepressin. Finally, promising strategies, involving monoclonal antibodies or protein antagonists, which selectively inhibit bacterial virulence factors are being assessed at the bedside. A much awaited and needed specific treatment for sepsis will hopefully soon emerge.